Performance Analysis of Three Phase Induction Motor at PT. Intracawood Manufacturing - Sartika, Linda; Huda, Abil; Prasetia, Abdul Muis; Sari, Lela Nofita (Muhammadiyah University, Sidoarjo, 2025)
To support the production process in an industry, there are many electric motor equipment in the form of induction motors. Induction motors are the most widely used motors in various fields, ranging from household environments to large-scale industries. Induction motors that are used continuously do not guarantee that they will always work normally, meaning that the motor can experience damage. These damages can affect the performance of the reduced induction motor. To find out the performance of the motor at PT. Intracawood Manufacturing, an analysis was carried out on the Blower Sander, Rotary, Conveyor Dry, and Conveyor Finishing motors, respectively on taking motor data based on the name plate and the motor in the current condition that was running or after rewinding. Motor performance analysis was conducted by calculating current, input power, output power, load torque, induction torque, and efficiency. From the calculation results, the Blower Sander motor by taking motor on the name plate with a current of 103 A, obtained an input power of 58.979 kW, an output power of 51.214 kW, an induction torque of 335.12 N.m, a load torque of 330.62 and efficiency of 86,83%. Meanwhile, the current motor condition with a current of 81.2 A, obtained input power of 43.945 kW, output power of 38.605 kW, induction torque of 254.7 N.m load torque of 250.23 N.m, and efficiency of 87.84%. Can be concluded, the performance of a three-phase induction motor at PT. Intracawood Manufacturing was a better is after rewinding.